Thoracic Epidural Analgesia: Does It Enhance Recovery?. Issue 12 (December 2018) - Rosen, David R.; Wolfe, Rachel C.; Damle, Aneel; Atallah, Chady; Chapman, William C.; Vetter, Joel M.; Mutch, Matthew G.; Hunt, Steven R.; Glasgow, Sean C.; Wise, Paul E.; Smith, Radhika K.; Silviera, Matthew L.
Abstract : BACKGROUND: Thoracic epidural analgesia has been shown to be an effective method of pain control. The utility of epidural analgesia as part of an enhanced recovery after surgery protocol is debatable. OBJECTIVE: This study aimed to determine if the use of thoracic epidural analgesia in an enhanced recovery after surgery protocol decreases hospital length of stay or inpatient opioid consumption after elective colorectal resection. DESIGN: This is a single-institution retrospective cohort study. SETTINGS: The study was performed at a high-volume, tertiary care center in the Midwest. An institutional database was used to identify patients. PATIENTS: All patients undergoing elective transabdominal colon or rectal resection by board-certified colon and rectal surgeons from 2013 to 2017 were included. MAIN OUTCOME MEASURES: The main outcome was length of stay. The secondary outcome was oral morphine milligram equivalents consumed during the first 48 hours. RESULTS: There were 1006 patients (n = 815 epidural, 191 no epidural) included. All patients received multimodal analgesia with opioid-sparing agents. Univariate analysis demonstrated no difference in length of stay between those who received thoracic epidural analgesia and those who did not (median, 4 vs 5 days; p = 0.16), which was substantiated by multivariable linear regression. Subgroup analysis showed that the addition of epidural analgesia resulted in no difference in length of stay regardless of an open (n = 362; p = 0.66) or minimally invasive (n = 644; p = 0.46) approach. Opioid consumption data were available after 2015 (n = 497 patients). Univariate analysis demonstrated no difference in morphine milligram equivalents consumed in the first 48 hours between patients who received epidural analgesia and those who did not (median, 135 vs 110 oral morphine milligram equivalents; p = 0.35). This was also confirmed by multivariable linear regression. LIMITATIONS: The retrospective observational design was a limitation of this study. CONCLUSION: The use of thoracic epidural analgesia within an enhanced recovery after surgery protocol was not found to be associated with a reduction in length of stay or morphine milligram equivalents consumed within the first 48 hours. We cannot recommend routine use of thoracic epidural analgesia within enhanced recovery after surgery protocols. SeeVideo Abstract athttp://links.lww.com/DCR/A765 .